Evaluating explanations for poverty selectivity in foreign aid. (3rd December 2021) - Heinrich, Tobias; Kobayashi, Yoshiharu
Abstract: Ending global poverty has been at the forefront of the development agenda since the 1970s, but many donors have failed to target their funds toward this goal. Activists have tackled this issue by appealing to donors' humanitarian motives, but we know little about what explains donors' decisions on how much to give to the poorest countries. This paper develops the donor motivation and foreign policy approaches and identify donors' development motives and their budget sizes as potential determinants of poverty selectivity. We evaluate their explanatory power by assessing whether their relationships with selectivity are in the hypothesized directions and generalize beyond a particular dataset. Employing cross‐validation and Bayesian Model Averaging, we find few measures of donor motivations provide a generalizable and hypothesized explanation for poverty selectivity. In contrast, donor budget sizes exhibit a relationship that is both hypothesized and externally valid. Our study offers the first systematic analysis of aid selectivity and generates implications for recent approaches to improve the quality of foreign aid and the conventional approach to study foreign aid allocation and donor motives.